Pendidikan Karakter Perspektif K.H. Hasyim Asy’ari - Mukani, Mukani (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2014)
Modern life brings significant changes in education. To respond, reorientation has been done, both in terms of curriculum, learning methodology, institutional management, educator qualifications and so on. In Indonesia, many educational leaders have conveyed their ideas in this context. One of them is KH. Hasyim Ash'ari. With the background of receiving traditional education, he is able to have a clear and systemic concept in education. So it is expected that the dynamics and modernization of education in Indonesia can be realized. By examining thirteen books written directly by KH. Hasyim Asy'ari, this study concludes that KH thought. Hasyim Asy'ari proved to be of great relevance in supporting the reform process of education in Indonesia, especially in giving the output of students character that is not only intelligently cognitive (pinter), but also concern for the society around (bener). However, it needs to be studied more deeply about the implementation and operational framework of KH thinking. Hashim Ash'ari, since it is still philosophical-theoretical.